Hypocholesterolemic effects of Balangu (Lallemantia royleana) seeds in the rabbits fed on a cholesterol-containing diet - Alireza Ghannadi; Ahmad Movahedian; Zahra Jannesary (Mashhad University of Medical Sciences, 2015)
Objectives: Lallemantia royleana (Benth. in Wall.) Benth. (Lamiaceae) is a medicinal plant used in Iranian traditional and folklore medicine in the treatment of various nervous, hepatic, and renal diseases. In the present study, whole seeds of the herb were prepared and evaluated for hypolipidemic activities using an animal model. Materials and Methods: Animals were fed normal diets or diets supplemented with cholesterol (0.5%) for 12 weeks to evoke hypercholesterolemia. Moreover, hypercholesterolemic animals were treated with different doses of whole seeds of Balangu (0, 5, 10, and 20%) for 12 weeks. Results: Results showed that the serum total cholesterol and triglyceride decreased in all groups treated with Balangu seeds pConclusions: Our results showed that L. royleana seeds decreased the serum cholesterol and triglyceride levels in hypercholesterolemic animals but led to the increase of atherogenic index in all treated groups.